Manajemen Konflik Dalam Perspektif Lembaga Pendidikan Islam - Arif Fiandi; Junaidi J (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to understand conflict management from an Islamic perspective. This research method is to use a literature review. The results of this research are that the occurrence of conflict in life is something that is natural and usually occurs. Conflict arises because of differences and contradictions in human behavior. Conflict must be managed well so that it becomes a force for the better. If conflict is left untreated and not managed with good conflict management, it will have bad and negative consequences. Islam is a religion that always provides solutions to all problems, including conflict management. One of the arguments for conflict management in Islam is contained in the letter Annisa' verse 35, which explains that conflicts must be resolved and solutions must be found.